IMPACT OF SOCIAL MEDIA ON SPORTS CLUBS DEVELOPMENT - D. Ilieva (Trakia Journal of Sciences)
The challenges sports clubs face today make social networks one of the critical components of their development. Social media has revolutionized the sports industry by changing the way athletes, coaches, clubs, federations, sport companies and other industry actors interact. Sports organizations are essential to the sporting world and significantly influence societies’ health, culture, and economics. The aimof this research was to examine and analyze the impact of social media on the development of sports clubs working in the field of sport for all. Main tasks are:to analyze the importance of interactive digital means in the work of sports organizations; toinvestigate the satisfaction and evaluation of target groups regarding social networks as a means of communication and their influence on clubs; to analyze the need of people in social networks as an opportunity for more effective development of sport forall clubs.The study was conducted among peoplepracticing sports, members of sports clubs –sport for all, members of the Bulgarian Sport for All Federation, who use social media. The subjectof the research was the influence of social media on the development of sports clubs.To fulfill the research tasks, it was created an online marketing questionnaire about various aspects of using social media in relation to the sports clubs “sport for all”. The research was also based on observing the sports clubs’ work, conducting an Internet-based survey, using mathematical-statistical methods, and analyzing specialized scientific sources. The analysis of this research would enable us to establish the degree of satisfaction and evaluation of the target groups regarding the use of social media as a means of communication and its influence on the activities of the clubs “sport for all”.